Desarrollo de un Prototipo para la Selección y Evaluación de Rasgos de Personalidad Obtenidos con la Prueba Psicotécnica 16PF por medio de Métodos de Aprendizaje Supervisado (2021)
This project shows the development of supervised learning software which allows to perform and evaluate the 16Pf test, this in order to avoid the shortcomings presented in the companies when practicing said tests. The software takes into account different parameters to arrive at a result such as the equations and tables of decapitation. The system is capable of evaluating 16 personality factors. The software was trained to determine whether or not the person is recommended for a company. These results are evaluated taking into account the guidelines that govern the qualification of the 16pf test. Finally, the software has the facility for the personnel in charge of said tests to have access to the database of users such as the test results, the evaluated factors, and the personal data of each applicant.